Policies for the prevention and control of Noncommunicable diseases in the WHO European Region: the example of salt - Siopa, Margarida Amorim Fernandes Rodrigues (2012)
Resumo da tese: As doenças não transmissíveis são responsáveis por mais de 80% das mortes na Região Europeia da Organização Mundial de Saúde. Dietas não saudáveis são um dos factores de risco mais relevantes e a redução do consumo excessivo de sal é uma das intervenções prioritárias na prevenção e controlo das doenças não transmissíveis. A implementação de políticas para a redução do consumo de sal nas populações, apesar de não estar no topo da agenda governamental, apresenta um custo-benefício e uma efectividade que deve ser tomada em consideração para melhorar o bem-estar e a qualidade de vida das populações. O envolvimento de parceiros, como a indústria alimentar e os media, com os diferentes organismos e associações nacionais e um correcto sistema de monitorização são a chave para o sucesso de uma política nacional de redução do consumo de sal, a fim de reduzir a ingestão de sal para 5g/dia, de acordo com a recomendação da Organização Mundial de Saúde. Um olhar atento nos diferentes sucessos das políticias na Região Europeia da Organização Mundial de Saúde poderá ajudar os países da Região, a implementar políticas nacionais bem estruturadas e eficazes com resultados benéficos para a Saúde.Thesis abstract: Noncommunicable diseases are responsible for more than 80% of deaths in the Member States of the World Health Organization European Region. Unhealthy diets are one of the most relevant risk factors and the reduction of excessive salt intake is a priority intervention in the prevention and control of noncommunicable diseases. The implementation of policies to reduce salt intake in populations, although not always a top priority on a government agenda, present a cost-beneficial and effective approach that must be taken into account to improve the welfare and quality of life of people. The involvement of partners such as the food industry and media, along with different agencies and national associations and a proper monitoring system is the key to the success of a national policy to reduce salt intake to 5g/day, the World Health Organization recommendation. A closer look at the different political successes in the World Health Organization European Region will help the countries across the Region to implement a well-structured and effective national policy with beneficial results to health.